The Commission of National Education and its transformation from 1773 to 1794 - Bartnicka, Kalina; Dormus, Katarzyna (Instytut Historii Nauki im. Ludwika i Aleksandra Birkenmajerów Polskiej Akademii Nauk, 2018)
The unexpected news about the suppression of the Society of Jesus by Pope Clement XIV arrived in Warsaw in September 1773 during the Sejm summoned for the purpose of ratifying the First Partition of the territory of the Polish–Lithuanian Commonwealth. The pope decided to subordinate the schools and the estate owned by the Jesuits to the secular clergy. Despite the pope’s recommendation, the parliamentarians decided to nationalise post-Jesuit schools and their estate. A central state office, the Commission of National Education, was established to supervise those schools. The post-Jesuit estate, converted into an educational fund under the authority of the Commission, would be used solely for the operations of schools and teachers as well as for a profound education reform. The Commission was instituted on 14 October 1773 and took charge of education and public schools without exceptions. In 1776, despite many obstacles, it assumed full control over its educational fund and commenced work immediately. Despite the belief generally held today, in its 20 years of existence, the Commission of National Education was significantly transformed on several occasions and did not operate without stopping. What was invariable were the concept and objective of the Commission and its schools: to raise an enlightened, public-oriented and happy man, a good citizen and patriot, capable of building a happy and wealthy society and a strong state. In 1795, Poland lost its independence for 123 years, but owing to the Commission’s activity, a new nation was born that was prepared to fight for its freedom.
Keywords: Commission of National Education; Polish–Lithuanian Commonwealth; partitions of Poland; suppression of the Jesuit Order; education system reform in 17th-century Poland